Comprehensive characterisation of multi-channel mixed-matrix membranes and impact of water matrix variability on micropollutant removal - Jana Marx; Jan Back; Felix Netzer; Tung Pham; Simon Penner; Rania Bakry; Martin Spruck (Case Studies in Chemical and Environmental Engineering)
Inadequate removal of micropollutants in wastewater treatment plants (WWTPs) contributes to environmental contamination, underscoring the need for effective technologies. Mixed-matrix membranes with embedded powdered activated carbon (PAC) show promise, but challenges remain, such as the potential loss of adsorption capacity of embedded PAC particles, limited performance data in different water matrices, and uncertain long-term regenerability. This study comprehensively characterised a specific multi-channel mixed-matrix membrane (MCMMM) and evaluated its micropollutant removal from various water matrices at different pH levels, comparing it to pure PAC and multi-channel membranes. Adsorption isotherms and kinetics were determined for the tested substances, as well as their removal during filtration. Although the BET surface area (563.5 m2/g) and static micropollutant capacity (166.8 mg/g) of PAC embedded in MCMMM were lower than those of pure PAC (884 m2/g, 232.6 mg/g), the capacity increased to 265.8 mg/g during dead-end filtration. Filtration of WWTP effluent demonstrated that the polymeric membrane matrix protected the embedded PAC from competitive adsorption with wastewater DOM and effects from water matrix pH were significant. Overall, this membrane type, with its distinctive characteristics and demonstrated regenerability, is highly influenced by the matrix of the treated water, laying the foundation for further long-term studies.